A man before his time: Russell's insights into nicotine, smoking, treatment and curbing the smoking problem. (15th November 2017) - McNeill, Ann; Robson, Debbie
Abstract: Background and aims: This narrative review aimed to provide a brief overview of five key research 'classics' produced by the innovative and radical thought leader, Professor Michael Anthony Hamilton Russell (1932–2009), drawing upon his other work wherever feasible. Methods: Narrative review. From more than 250 publications, we selected papers we considered seminal texts, published in 1971, 1976, 1978, 1979 and 1991. Results: Russell was among the first researchers to explain that smoking was a dependence disorder caused by the drug nicotine decades before this was recognized formally. He therefore saw quickly the importance of delivering nicotine in a less harmful format as a way of controlling nicotine withdrawal when stopping smoking, first studying nicotine gum. In addition to pharmacotherapies, Russell's research also explored the role of behavioural support, particularly the role of general practitioners (GPs), alone as well as supported by specialist clinics; this research underpinned initiatives in England to reimburse doctors for giving advice to smokers, and to provide a national network of smoking cessation services. Research on nicotine uptake from other delivery systems and routes led Russell to theorize that the speed and dose of delivery impacted upon the effectiveness of a product to act as a substitute for smoking. He commented on the addictiveness of the high nicotine boli delivered in quick succession when smoking cigarettes and argued that alternative recreational nicotine delivery systems would need to be promoted actively to smokers in order for them to compete with cigarettes, a forerunner for contemporary debates on electronic cigarettes. Conclusions: The legacy of Russell's landmark research is seen in present‐day nicotine science, policy and discourse.